2021
DOI: 10.1016/j.jad.2021.05.121
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 dimensions are related to depression and anxiety among US college students: Findings from the Healthy Minds Survey 2020

Abstract: Background The COVID-19 pandemic has brought about tremendous social and economic turmoil, which has been associated with increased levels of depression and anxiety. Methods We analyzed data from the Healthy Minds Study (Fall Semester Cohort 2020), a non-probability sample of students across multiple colleges who completed an online survey between September – December 2020. Using multivariable logistic regression, we examined the associations between COVID-19 dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 42 publications
1
54
0
3
Order By: Relevance
“…Moreover, they could not expect their families to understand the particular pressures associated with being college students. Research already suggests a link between financial distress as a result of COVID‐19 challenges and increased anxiety and depression among US college students (Oh, et al., 2021). However, this line of research has yet to consider the role of student social class on the amount of concern for their finances and thus on their levels of anxiety and depression despite research that shows first‐generation college students (who likely come from lower‐income backgrounds or parents with less stable jobs) report fewer protective mental health factors than nonfirst‐generation college students (Jeong et al., 2021).…”
Section: Stress and Changementioning
confidence: 99%
“…Moreover, they could not expect their families to understand the particular pressures associated with being college students. Research already suggests a link between financial distress as a result of COVID‐19 challenges and increased anxiety and depression among US college students (Oh, et al., 2021). However, this line of research has yet to consider the role of student social class on the amount of concern for their finances and thus on their levels of anxiety and depression despite research that shows first‐generation college students (who likely come from lower‐income backgrounds or parents with less stable jobs) report fewer protective mental health factors than nonfirst‐generation college students (Jeong et al., 2021).…”
Section: Stress and Changementioning
confidence: 99%
“…From the beginning of the COVID‐19 outbreak, people have experienced elevated psychological distress in their everyday lives (e.g., Akbari, Seydavi, et al, 2021 ; Brailovskaia et al, 2021 ; Cao et al, 2020 ; Chen et al, 2021 ; Duong, 2021 ; Kontoangelos et al, 2020 ; Lee, 2020 ; Mansueto et al, 2021 ; Shevlin et al, 2020 ) including depression and anxiety (Huang & Zhao, 2020 ; Oh et al, 2021 ; Wierenga et al, in press ), obsessive–compulsive symptoms (Abba‐Aji et al, 2020 ; Seçer & Ulaş, 2020 ; Wheaton et al, 2021 ), substance use (Akbari et al, 2020 ; Czeisler et al, 2020 ), post‐traumatic stress symptoms (Akbari, Hosseini, et al, 2021 ; Johnson et al, 2020 ; Liu et al, 2020 ), suicidal ideation (Czeisler et al, 2020 ), health anxiety (Akbari, Spada, et al, 2021 ; Özdin & Özdin, 2020 ), psychological distress (Wang et al, 2020 ; Wu et al, 2020 ), hopelessness (Hacimusalar et al, 2020 ), loneliness and fatigue (Hou et al, 2020 ; Mansueto et al, 2021 ), loss and grief (Wallace et al, 2020 ; Zhai & Du, 2020 ), sleep problems (Duong, 2021 ; Jahrami et al, 2021 ) and reduced life satisfaction (Duong, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has exacerbated this alarming mental health trend. Eighty percent of college students report that pandemic-related closures of college campuses have negatively impacted their mental health ( Active Minds, 2020 ; López-Castro et al, 2021 ; Oh et al, 2021 ). Recent authors have identified dramatic increases in alcohol use among college students as a coping mechanism during the COVID-19 pandemic ( Bonar et al, 2021 ; Buckner et al, 2021 ; Coakley et al, 2021 ; Jackson et al, 2021 ).…”
mentioning
confidence: 99%